2018
DOI: 10.1039/c7cp07593f
|View full text |Cite
|
Sign up to set email alerts
|

Transport and accumulation of plasma generated species in aqueous solution

Abstract: The interaction between cold atmospheric pressure plasma and liquids is receiving increasing attention for various applications. In particular, the use of plasma-treated liquids (PTL) for biomedical applications is of growing importance, in particular for sterilization and cancer treatment. However, insight into the underlying mechanisms of plasma-liquid interactions is still scarce. Here, we present a 2D fluid dynamics model for the interaction between a plasma jet and liquid water. Our results indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
109
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(123 citation statements)
references
References 75 publications
5
109
0
Order By: Relevance
“…The flow pattern is shown in Figure 5e, where the flow pattern in the liquid is clearly visible in the density profiles of dissolved species with high Henry's constant. [ 135,136 ] Following the liquid flow pattern shown in Figure 5d, the aqueous plasma active species initially remained at the plasma‐liquid interface and accumulated in the reverse vortex. They also flow back to the liquid surface, following the flow pattern, after which they return into the bulk liquid.…”
Section: Transport Of Reactive Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The flow pattern is shown in Figure 5e, where the flow pattern in the liquid is clearly visible in the density profiles of dissolved species with high Henry's constant. [ 135,136 ] Following the liquid flow pattern shown in Figure 5d, the aqueous plasma active species initially remained at the plasma‐liquid interface and accumulated in the reverse vortex. They also flow back to the liquid surface, following the flow pattern, after which they return into the bulk liquid.…”
Section: Transport Of Reactive Agentsmentioning
confidence: 99%
“…They also flow back to the liquid surface, following the flow pattern, after which they return into the bulk liquid. [ 136 ] The gaseous plasma active species with low Henry's constant accumulated in the gas phase just above the plasma‐liquid interface, leading to a much lower concentration in the liquid phase.…”
Section: Transport Of Reactive Agentsmentioning
confidence: 99%
“…NTP–liquid reactions—formation of reactive species at different sections (Liu et al., ; Verlackt et al., ).…”
Section: Ntp–liquid Interactionsmentioning
confidence: 99%
“…From Figure 2, it can be inferred that all the stable high-concentration reactive species in liquid are mainly produced by the diffusion process. As the experimental validation of the distribution and penetration (Liu et al, 2016;Verlackt et al, 2018). Anderson (2016) HNO 2 and HNO 3 2.5 × 10 −5 Anderson (2016) characteristics of reactive species is difficult to measure, these parameters and mass transfer kinetics are mostly evaluated using numerical simulation techniques (Bie et al, 2016;Chen, Tao, et al, 2014;Jiang et al, 2016;Thagard et al, 2016;Yusupov et al, 2013).…”
Section: Ntp-liquid Interactionsmentioning
confidence: 99%
“…The extended timescale may be long enough for these reactive species to reach the surface of a target (biological material) or a liquid medium and activate that surface despite the majority of primary species having already reacted away. Results from the modeling of argon plasma jets onto water by Verlackt et al showed that aqueous reactive species can either originate from the gas‐phase plasma or be formed at the liquid interface. They found that densities of H 2 O 2aq , HNO 2aq /NO 2 − aq and NO 3 − aq increase in solution as a function of time, while the densities of O 3aq , HO 2aq /O 2 − aq , and ONOOH aq /ONOO − aq quickly saturate.…”
Section: Introductionmentioning
confidence: 99%